New Opportunities to Prevent Postoperative Complications in Abdominal Surgery (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Prevention of postoperative complications remains one of the urgent problems of modern surgery. Despite the improvement of means and methods of antiseptic, perioperative antibiotic prophylaxis, the number of postoperative purulent complications remains high and reaches 4-17% after middle laparotomy operations The increase in the number of postoperative complications is associated with the performance of more complex, prolonged operations, the development of transplantology, the increase in the life expectancy of the population and others. Postoperative complications significantly increase the duration of patients' stay in the hospital.